Effects of biochar and organic fertilizer on the plant growth and control of root knot nematode disease of kenaf (Hibiscus cannabis) - Norhayati, Ngah; Siti Nur Fatihah, Hashim; Az'wafa, Rozali; Mohammad Hailmi, Sajili; Tajul Afif, Abdullah; Abd Jamil, Zakaria; Salmah, Mohamed; Mohd Norsyam, Yahaya; Kamaruddin, Mokhtar (2021)
Kenaf (Hibiscus cannabinus) is cultivated for its fiber. In Malaysia, this crop was grown at the BRIS soil area; which was previously cultivated with tobacco plant. BRIS soil is known as unfertile soil and need to be treated to improve the growth of plant. In this study, the effect of BRIS soil treated with biochar and its combination with other organic fertilizer on the growth of kenaf and its consequence effect on plant resistancy against root knot nematode disease were investigated. The design for the experiment was CRD (complete randomized design) with ten replicates. The plot size was 5 meter x 5 meter each. Treatments are (1) chemical fertilizer (NPK), (2) biochar, (3) biochar: cow dung, (4) biochar: organic compost and (5) biochar: cow dung: organic compost with the ratio 1 to 1. The plant growth parameters such as plant height, chlorophyll content, plant biomass and fiber dry weight were measured at the end of the study. The roots of plant were collected to investigate the indirect effect of these treatments on the plant resistancy against root knot nematode disease. Despite of having the significantly higher number of nematode galls on plant roots, results obtained shows that the application of chemical fertilizer was significantly improved the growth of kenaf compared to other treatments. On the other hand, eventhough the number of nematode galls found on plant roots at the plot treated with biochar is significantly lower compared to other treatments, biochar application does not improve the plant growth performance.